I PREFER TO STAY SILENT”: STUDENTS’ NARRATIVES OF TEACHER DOMINANCE IN ELT CLASSROOM - Bahar; Dahlia Husain; Ana Mariana (University of Kuningan, 2026)
Speaking is frequently positioned as the most visible indicator of success in English as a Foreign Language (EFL) learning, yet many Indonesian classrooms still show minimal student oral participation even in higher education. This study explores how learners narrate teacher power in EFL speaking lessons and how these interactional patterns shape psychological barriers that ends up in classroom silence. Using an interpretive qualitative design, the research was conducted at Fajar University, Indonesia. Unstructured, in-depth interviews were conducted in Indonesian with ten EFL students and one English lecturer to reduce language constraints on disclosure. Data were analyzed through iterative thematic coding, constant comparison, and theme refinement. The study revealed that power enactments were linked to four mutually reinforcing consequences: lowered speaking self-confidence, heightened fear of negative evaluation and punishment, weakened motivational intensity, and boredom-driven disengagement. Under such conditions, silence operated less as evidence of inadequate linguistic competence than as a rational strategy of self-protection within a high-risk, low-reward communicative environment. The study contributes a student-centered account of how everyday classroom routines operationalize power in speaking instruction and suggests that transforming authority from coercive control to supportive guidance is crucial for fostering willingness to communicate. Pedagogical implications include face-sensitive feedback, expanded wait time and turn allocation, negotiated topics, and psychologically safe participation norms to sustain ongoing speaking engagement for learners.